Legal Nature of Terrorist Crimes in Russian Legal System - Babichev, Arseniy Georgievich; Khakimova, Elmira Robertovna (Ius Humani. Jornal do direito, 2021)
The article examines the legal nature of terrorism from the Russian legal system point of view. The relevance of the research stems from the large scale, sophistication, and cruelty with which terrorist crimes have been committed over the recent decades. Terrorism has nowadays become a global threat, and any government, including government of the Russian Federation, must take it into consideration when formulating its domestic and foreign policy. In countering terrorist crimes, current regulations of the Criminal Code of Russian Federation take rather important part. Punishment differentiation, depending on corpus delicti and consequences, as well as correct qualification of terrorist crimes, are the most important conditions of those regulation's efficient application. This problem is in fact interdisciplinary one, which is proved by researchers from other scientific fields: not only law scientists, but also psychologists, historians, political scientists. All the listed illustrates relevance, timeliness, and expediency of researching the problems mentioned. The purpose of the study is formulating recommendations for solving the above-mentioned issues of improving the existing criminal (and other) measures and developing new viable and practically applicable criminal measures for countering terrorist crimes.